Simple, Accurate and Precise Determination of the Fungicide Zoxamide in Wine and the Characterization of its Stability in Gastric Conditions by Reverse-Phase High-Performance Liquid Chromatography (RP-HPLC) - Borahan, Tulay; Unutkan, Tugce; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2020)
A rapid, accurate and precise method based on reverse-phase high performance liquid chromatography (RP-HPLC) was developed for the trace determination of zoxamide in wine samples. The chromatographic separation was performed at room temperature on a C18 column using mobile phase comprised of methanol and water (82/18, v/v) with a 1.0 mL min(-1) flow rate. The analyte was detected at 254 nm. The method was validated based on the accuracy, linearity, precision, and limits of detection and quantification. The linearity of the presented method was found to be in the range from 5.0 mu g L-1 to 200 mg L-1 with a correlation coefficient of 0.9999 and a low relative standard deviation (< 10%) for the lowest concentration of the calibration plot, demonstrating suitable precision. The limits of detection and quantification were determined to be 1.9 and 6.2 mu g L-1, respectively. The applicability and the accuracy were studied by performing recovery studies on wine samples. The percent recoveries were obtained in the range between 96.7 and 101.5%. The stability and the properties of the analyte were also investigated under simulated gastric conditions. No change in the peak height and area and the retention time of the analyte were observed throughout a 300 min time period.
Keywords: Fungicide; simulated gastric juice; reverse-phase high-performance liquid chromatography (RP-HPLC); zoxamide; MASS-SPECTROMETRY; PESTICIDES; EXTRACTION; RESIDUES; Chemistry